Seismic Floor Response Characteristics of Sloped Roof in Traditional Masonry Structural System Due To Strong Bi-Directional Ground Motions - Thusa, Bidhek; Thusa, Bidhan; Prajapati, Amit (Journal of Science and Engineering, 2026)
The recent failure of the sloped roof of the ancient pagoda, Fengyang Drum Tower in eastern China, has raised major concerns about the safety of such a structure. The primary objective of this study is to investigate the engineering demand parameter of a sloping roof in a traditional pagoda masonry structure. Generally, most traditional masonry structures consist of steep, sloping roofs with an angle ranging from 25 to 30 degrees. These roofs carry a large amount of self-weight as well as are supported by the wooden roofing system. These roof systems are critical in terms of public safety during the earthquake evacuation process. They are highly vulnerable to damage due to their location and experience maximum acceleration during earthquakes. The damage on sloped roofs is a critical hazard scenario for a traditionally dense city like Bhaktapur. This study selects a typical pagoda masonry structure for simulating the seismic response of such structures and locates the critical local and global locations of importance. The numerical model is developed utilizing three-dimensional nonlinear shell elements in SAP2000. This study utilizes 10 strong bi-directional natural ground motions for the time history analyses. The global and local structural response due to input strong bi-directional ground motion is investigated. The uni-directional and bi-directional responses are compared to investigate the effect of bi-directional ground motions on response characteristics. Additionally, this study investigates the global response trajectory of the system due to bi-directional ground motion for the precise seismic response characterization. The critical angle of incidence of the traditional pagoda structures is also investigated. This study points out the importance of considering bi-directional ground motions for efficient seismic performance evaluation of such structures. This study recommends updating design code and provisions to address the bi-directional effect of ground motions during structural analysis and seismic performance evaluations of existing structures.